Establishment of a Zimbabwe national SME sector: A major priority to enhance the performance of the national economy - Godfrey Tambudzayi Musabayana; Emmanuel Mutambara; Tony Ngwenya (Journal of Innovation and Entrepreneurship, 2023)
A sound administration strategy is an effective tool to improve the performance SMEs. The establishment of a national SME sector will assist in the implementation, monitoring and evaluation of programmes that aim to improve the performance of SMEs. The administration of the SMEs by the Ministry of Women affairs, Community and Small and Medium Enterprises Development has failed to improve the performance of SMEs. This study established that the administration of SMEs by the ministry lacks value addition and value creation, technological innovation and research and development and it is disjointed from the implementers, hence the need to establish a new Zimbabwe National SME sector which can improve the performance of SMEs. The mixed method research was used in the study following the sequential exploratory strategy which employed both qualitative and quantitative data collection methods. The study followed the dominant sequential mixed strategy which collected data in two phases. The findings of the study will assist the government to establish a new SME sector that will address the plight of the SMEs. From the study, the researcher deduces that the ministry responsible for SMEs is overwhelmed with responsibilities and is not reaching out to the SMEs. The researcher proposed the structure of a new Zimbabwe National SME sector that focusses on the improvement of SME performance.
Keywords: 650; Research and development; SME sector; Technological innovation; Value addition and creation